Development of a Social Arithmetic Teaching Module Based on the Indonesian Realistic Mathematics Education Approach to Support the Numeracy Skills of Junior High School Students - Chealsea Medeline Somba; Ichdar Domu; Navel Oktaviandy Mangelep; Patricia V. J. Runtu; Nicky K. Tumalun (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to develop a social arithmetic teaching module based on the Indonesian Realistic Mathematics Education (PMRI) approach that is valid, practical, and effective in supporting the numeracy skills of junior high school students. The low numeracy achievement of Indonesian students, reflected in the 2022 Programme for International Student Assessment (PISA) score of 366, together with the limited availability of contextual teaching materials, motivated this research. The study employed the Research and Development method using the Plomp model, which comprises three phases: preliminary research, the development or prototyping phase, and the assessment phase. The research subjects were seventh-grade students of SMP Katolik Don Bosco Bitung in the 2025/2026 academic year. Data were collected through expert validation sheets, teacher and student practicality questionnaires, and numeracy tests (pretest and posttest), then analysed using percentage scores and the N-Gain formula. The results show that the module met the highly valid criteria with percentages of 90% from the material expert and 91.7% from the media expert, while the test instrument reached 90%. The practicality aspect was categorised as highly practical based on the one-to-one trial (85.2%), small-group trial (88.8%), and field test (85.34%). The module's effectiveness was demonstrated by an increase in students' average scores from 28.63 on the pretest to 65.91 on the posttest, with an N-Gain value of 0.51 in the medium category. Therefore, the developed PMRI-based social arithmetic module is feasible for use as teaching material that supports the numeracy skills of junior high school students.